1986
DOI: 10.1346/ccmn.1986.0340508
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Vermiculite in Adirondack Soils and Till

Abstract: Abstract--The clay and bulk mineralogy of soil and till from 26 Adirondack watersheds was studied. The materials consist typically of quartz, K-feldspar, plagioclase, mica, vermiculite, and kaolinite. Talc, smectite, halloysite, and hornblende are present in some samples. The clay fraction of the soils is composed predominantly of vermiculite, likely derived from the transformation of a mica precursor, and kaolinite. The soil vermiculite commonly contains hydroxy-Al interlayers which are especially prevalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 19 publications
4
35
0
Order By: Relevance
“…The origin of the trioctahedral variety of vermiculite remains unclear (Justo et al, 1986;de la Calle and Suquet, 1988;Zhelyaskova-Panayotova et al, 1992 whereas the dioctahedral variety is unquestionably accepted as the product of low-temperature surface weathering (Gruner, 1939;Hathaway, 1955;Barshad and Kishk, 1969;April et al, 1986;Graham et al, 1989;Moon et al, 1994). Experimental studies produced vermiculite as an alteration product of micas Toksoy-Krksal, Ttirkmeno~lu, and GOnciao~lu Clays and Clay Minerals owing to the effects of low-alkali solutions (Komarneni and Roy, 1981).…”
Section: Inductively Coupled Plasma Spectrometry Analysismentioning
confidence: 99%
“…The origin of the trioctahedral variety of vermiculite remains unclear (Justo et al, 1986;de la Calle and Suquet, 1988;Zhelyaskova-Panayotova et al, 1992 whereas the dioctahedral variety is unquestionably accepted as the product of low-temperature surface weathering (Gruner, 1939;Hathaway, 1955;Barshad and Kishk, 1969;April et al, 1986;Graham et al, 1989;Moon et al, 1994). Experimental studies produced vermiculite as an alteration product of micas Toksoy-Krksal, Ttirkmeno~lu, and GOnciao~lu Clays and Clay Minerals owing to the effects of low-alkali solutions (Komarneni and Roy, 1981).…”
Section: Inductively Coupled Plasma Spectrometry Analysismentioning
confidence: 99%
“…For example, vermiculite forms in the A horizon at the same time hydroxy-A1 vermiculite forms in the deeper B horizons of certain Adirondack soils (April et aL, 1986). This distribution can be explained by the presence of organic acids (especially citric and oxalic acids formed under aerobic conditions) from the overlying leaf-litter that prevent the formation of hydroxy-Al interlayers in the vermiculites at near-surface depths (Vicente et aL, 1977;April et aL, 1986).…”
Section: Chlorite Vermiculitizationmentioning
confidence: 99%
“…Hydroxy-A1 vermiculites form by intense weathering under acid conditions and are stable with respect to vermiculite (and possibly kaolinite) in many weathering horizons (Douglas, 1977). However, there are some exceptions and April et al (1986) suggested that organic acids from leaf litter, or the establishment of more aggressive weathering regimes, had remobilized hydroxy-A1 interlayers producing vermiculite in an Adirondack soil.…”
Section: Introductionmentioning
confidence: 99%
“…Many workers have studied this process by observing both naturally weathered micaceous minerals and mica altered artificially in the laboratory. Supergene vermiculitization of trioctahedral micas through intermediate stages ofinterstratified mica/vermiculite has been identified as one of the main mineral weathering sequences reported in the literature (Coleman et al, 1963;Rhoades and Coleman, 1967;Meunier and Velde, 1979;April et aL, 1986;Ildefonse et al, 1986;Banfield and Eggleton, 1988;Bain et aL, 1990;Fordham, 1990a). Vermiculite deposits at Cheongyang, South Korea, appear to be derived from both phlogopite in ultramafic and biotite in mafic intrusive rocks (Song et aL, 1990).…”
Section: Introductionmentioning
confidence: 99%